Ecostructure and Endemicity of Plant Species in Lowland Plantation Typology (Hortipark) Karang Sidemen Village, West Nusa Tenggara - Niechi Valentino; Muhamad Husni Idris; Andrie Ridzki Prasetyo; Musdi, Musdi; Rima Vera Ningsih; Muhammad Anwar Hadi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
The richness of local resources and the ecosystem potential of a village, one of which is the uniqueness of the lowland plantation ecosystem (hortipark), is the main key in supporting the success of sustainable rural development. The main focus of the research is to reveal the ecostructure and endemicity of plant biodiversity in the lowland plantation typology of Karang Sidemen Village, NTB. Data collection in the field used a systematic sampling design with random start method for 12 research plots. The results of observations found 1116 individuals, 29 tribes, 59 genera and 59 plant species at all levels of habitus, and there were 20 plant species endemic to Lesser Sunda. The highest INP tree is Ceiba pentandra (L.) Gaertn. (111.79%), stake rate of Tectona grandis Lf (136.97%), stake rate of Persea americana Mill. (82.86%), Dendrocnide stimulant (Lf) Chew seedling rate (130.48%), Musa × paradisiaca L. shrub rate (81.28%), Panicum brevifolium L. herb rate (32.53%), Chloranthus erectus (Buch-Ham) shrub rate) Wall. (46.64%), the level of the fern Macrothelypteris torresiana (71.22%) and the level of the liana Centrosema pubescens Benth (96.99%). The concentration of horizontal structures is in diameter classes 2 and 4 while the concentration of vertical structures is in class 1. The H' Index range has values ​​in the low - medium category with the highest H' being at the livestock level of 2.64. The E' index is in the medium - high category with the highest E' at the shrub level of 1.00. The R1 index is in the low - medium range, with the highest R1 at the livestock level of 3.45. The distribution of plant species is mostly clustered, especially at the herb level. Based on the Raunkiaer frequency class law, it is known that species in the lowland hortipark plantation ecosystem of Karang Sidemen Village are included in the type of artificial ecosystem with the highest frequency in class A (1-20%).